An Overview of Microwave‐Assisted Kabachnik‐Fields Reactions. Issue 15 (17th April 2020) - Shilpa, Thomas; Ann Harry, Nissy; Ujwaldev, Sankuviruthiyil M.; Anilkumar, Gopinathan
Abstract: A comprehensive evaluation of MW‐assisted Kabachnik‐Fields reactions (phospha‐Mannich condensation) is done to draw the attention of synthetic chemists towards a greener, solvent‐free and catalyst‐free protocol. The review encompasses the diverse class of α‐aminophosphonates and its derivatives synthesized via one‐pot three component KF reaction, which finds application in various disciplines of chemistry and covers literature up to 2020. Abstract : One‐pot three component MW‐assisted KF reaction to produce novel organophosphorus compounds that are highly desirable as Pharmaceuticals, Agrochemicals and Fluorescent Organic Nanoparticles (FONs).